Analysis of clinical characteristics and imagological features of the aortic dissection patients with negative D-dimer results - Zhang, Zhixiang; Wang, Lilan; Su, Xin; Zhou, Yuling; Wu, Kaimin; Sun, Guangfeng; Ou, Weimei; Yu, Lihong; Chen, Weifen; Wang, Bin (Frontiers in Cardiovascular Medicine, 2023)
Background D-dimer (DD) is a vital biomarker to rule out the diagnosis of aortic dissection (AD). However, the DD level in some patients with AD is not high in clinical practice, which often leads to missed diagnosis; therefore, understanding the characteristics of patients with AD and negative DD is of great clinical value. Methods From May 2015 to October 2020, 286 patients with AD who visited the first medical contact (FMC) within 24 h of symptom onset and were hospitalized in the Xiamen Cardiovascular Hospital of Xiamen University were enrolled in this study. Clinical characteristics and outcomes of patients were assessed. Results Among them, 13 cases (approximately 4.5%) had negative DD results. Compared to patients with positive DD results, patients with negative DD results had significantly higher platelet counts and lower aortic dissection detection risk scores (ADD-RS). The imagological analysis showed that patients with AD and negative DD had lower extension scores and milder damage to the mesenteric artery and three branches of the aortic arch. Furthermore, the results of the multivariable analysis showed that white blood cell count (WBC) [odds ratio (OR): 1.379, P = 0.028], FMC (OR: 0.904, P = 0.028), and extension score (OR: 1.623, P = 0.046) were associated with negative DD result. Conclusions Patients with AD and negative DD results had longer FMC and lower WBC. Imaging showed a smaller tear extension range and less damage to the mesenteric artery and three branches of the aortic arch. A negative DD result could not completely rule out AD even if the ADD-RS was zero.